Social-informational competency of journalists - Альсадун, М. А. (Scientific notes of the pedagogical department, 2019)
The article is devoted to the definition of the essence of the social-informational competence of journalists. The author of the article adheres to the position that the fundamental changes in the professional training of specialists have brought a new level of attention to key competencies, among which the priority is this competence. For future journalists, it is the basic one, because due to its formation, the professional functions of these specialists are systematically implemented. A consecutive analysis of each of its components is carried out in order to logically approach the definition of the essence of the basic concept of research. By analyzing each of them, the author determines their specificity regarding the professional activities of journalists. At the same time, social competence is defined as personal education, which allows the journalist to effectively interact both individually and in a team when processing large information flows thanks to knowledge and skills in implementing a communicative channel.The author shows that information competence allows the journalist to realize his ability to determine the relevance of his chosen problems; to meet the required deadlines for the creation of the necessary material, using the information and expert base for this, taking into account the format of the publication for which the material is being prepared. It is determined that the journalist's social and informational competence is autonomous. It is defined as the integrative quality of the personality, which characterizes its ability to select, process, transforms information and enables to organize effective professional communication based on the use of modern communicative technologies in the process of individual or team work. Based on the analysis of literature and personal retrospective experience, the author determined the content of this competence through the necessary knowledge, skills and abilities of the journalist.